2020
DOI: 10.2478/subboec-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

Internal Branding: Antecedents of Employee Attitudes, Satisfaction, and Organizational Loyalty

Abstract: As competition between employers has become more intense in recent years, employee-based differentiation has become one of the strategic solutions for many organizations. The objective of this paper is to test a nomological model between internal branding, attitude, satisfaction, and loyalty. Data were collected through a survey among employees of a leading electronics conglomerate from Romania. While the relationship between attitudes and loyalty is partially mediated by satisfaction, the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Studies always indicated that employees who perceived strong emotional, instrumental and informational support from their managers demonstrated higher engagement and job satisfaction (Scridon, 2020). Supportive management practices enhanced commitment, productivity, retention and innovation among employees, fostering a positive work environment conducive to building brand equity (Pahlberg, 2009; Nurul Ezaili et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies always indicated that employees who perceived strong emotional, instrumental and informational support from their managers demonstrated higher engagement and job satisfaction (Scridon, 2020). Supportive management practices enhanced commitment, productivity, retention and innovation among employees, fostering a positive work environment conducive to building brand equity (Pahlberg, 2009; Nurul Ezaili et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Motivated employees contribute to job satisfaction, productivity and commitment to organisational goals, ultimately influencing brand success (Bin Majid and Hanaysha, 2018; Dartey-Baah, 2010). Training and development equip employees with the knowledge and skills to represent the brand effectively and create a culture of continuous improvement (Scridon, 2020). Knowledge dissemination fosters unity, collaboration and a positive brand image, enabling employees to access valuable resources to support their professional growth (Liu, 2022).…”
Section: Resultsmentioning
confidence: 99%